"You Get Beautiful Teeth Down There": Racial/Ethnic Minority Older Adults' Perspectives on Care at Dental School Clinics. Issue 11 (1st November 2017) - Northridge, Mary E.; Schenkel, Andrew B.; Birenz, Shirley; Estrada, Ivette; Metcalf, Sara S.; Wolff, Mark S.
Abstract : To help eliminate reported racial/ethnic and socioeconomic inequities in oral health care, listening to the perspectives of racial/ethnic minority older adults on their experiences with dental school clinics is needed. The aim of this study was to examine the experiences of African American, Puerto Rican, and Dominican older adults who attend senior centers in upper Manhattan, New York City, regarding the care received at dental school clinics. Focus groups were conducted from 2013 to 2015 with 194 racial/ethnic minority men and women aged 50 years and older living in upper Manhattan. All of the 24 focus group sessions were digitally audiorecorded and transcribed for analysis. Groups conducted in Spanish were transcribed first in Spanish and then translated into English. Analysis of the transcripts was conducted using thematic content analysis. Seven subthemes were manifest in the data related to these adults' positive experiences with dental school clinics: excellent outcomes and dentists, painless and safe treatment, affordable care, honest and reputable, benefits of student training, accepting and helpful, and recommended by family and friends. Negative experiences centered around four subthemes: multiple visits required for treatment, loss of interpersonal communication due to use of technology, inconvenient location, and perceived stigma with Medicaid. This study provided novel evidence of the largely positive experiences with dental schools of racial/ethnic minority senior center attendees. Interventions targeted at the organization and provider level, including organizational motivation, resources, staff attributes, climate, and teamwork plus payment programs and services, insurance and affordability, and provider‐ and system‐level supports, may improve health care processes and patient experiences of care.